The structure of glassy HgS-GeS2 - Halian, Volodymyr V.; Davydiuk, Heorhii Ye.; Parasyuk, Oleh V.; Kevshyn, Andrii H.; Галян, Володимир Володимирович; Давидюк, Георгій Євлампійович; Парасюк, Олег Васильович; Кевшин, Андрій Григорович (Інститут фізики напівпровідників ім. В.Є. Лашкарьова НАН України, Технологічний парк "Напівпровідникові технології та матеріали, оптоелектроніка і сенсорна техніка", Українське відділення Міжнародного товариства оптичної техніки, 2005)
The glass HgS(x)-GeS2(100-x) (0 ≤ x ≤ 50) was subjected to X-ray analysis. The radial distribution functions were calculated using the integral Fourier transformation based on X-ray scattering curves. The average interatomic distances within the first and second coordination spheres were determined. It is suggested that the transformational changes of scattering curves are related to the emergence of heterogeneity due to Hg4GeS6 inclusions.
Keywords: glassy alloy; radial distribution function; average interatomic distances; heterogeneity